The Analysis Potentials and Sustainablity Development of Agro-Ecotourism In Palopo, South Sulawesi - Rahmat, Rahmat; Hakim, Abdul; Riniwati, Harsuko; Yasin, Hasnidar (Journal of Indonesian Tourism and Development Studies, 2020)
Latuppa Area in Palopo is located in the northern part of South Sulawesi Province. It has some potential cultural and natural tourism spots to develop using the concept of agro-ecotourism. Sustainable tourism is considered as a step to manage all resources socially and economically. It can be done by preserving the cultural integrity, basic ecological processes, biological diversity, and other life support elements. This study was aimed to determine the potential attraction and to analyze the sustainability status and to construct the model of Latuppa agro-ecotourism development in Palopo, South Sulawesi. The model of sustainable agro-ecotourism development in Palopo, South Sulawesi Province, was conducted with qualitative and quantitative research method, using MDS and analysis of SWOT. The result of the index value of sustainability from five dimensions is 59.39. It means that by paying attention on the dimension aspects of ecology, economy, socio-cultural, technology, and institution at Latuppa, agro-ecotourism area can support the agro-ecotourism.The results of SWOT analysis that can be applied in the analysis of the strategy for the sustainable Latuppa agro-ecotourism development are as follows. The strategies are creatinga new tourist attraction to attract the tourists, educating the local community in terms of tourism management, developing tourism products, and promoting tourism objects.Keywords: agro-ecotourism, development, ecology, sustainablity.